Estimación de la filtración glomerular por medio de la formula CKD- EPI en pacientes que acuden al laboratorio del Hospital Isidro Ayora de Loja - Chamba Iñiguez, Andrea del Rocío (2017)
The CKD-EPI equation and creatinine clearance are the most commonly used methods for measuring the estimated glomerular filtration rate and thus the degree of chronic renal disease (CKD). The objective of this study was to evaluate the usefulness of the use of the CKD-EPI formula in the early diagnosis of renal diseases, for which 300 data were analyzed of patients who went to the Isidro Ayora Hospital in the city of Loja during the July period - August 2016; Age, sex, race, serum creatinine, and creatinine clearance were determined in a group of individuals to perform the correlation test. 70.4% of the data correspond to the female sex and 2.6% to the male; 60.8% in stage 1, 26.4% in stage 2, 6.8% in stage 3, 2.6% in stage 4 and 3.5% in stage 5. Stages 3, 4 and 5 represent 10 % And are under 70 years